Gross Morphologic Study of Femur Bone in Kenguri Sheep - Awate, Annapurna (Indian Journal of Veterinary Anatomy, 2020)
The study was undertaken on the femur bone of Kenguri sheep to know the gross morphology and its development at different age levels in Kenguri sheep. The left and right femur bones from 24 animals of both sexes were divided into four groups. Femur showed cylindrical shaft. The lateral and posterior surfaces were separated by a distinct line and was appreciated from 3 months onwards and later well developed. The supracondyloid fossa was bounded laterally by a supracondyloid crest at 3 months of age, later developed into tuberosity. The lesser tronchanter noticed as small round button like structure and completely not fused with the shaft in group-I animals, later well developed and completely fused with the shaft in other three groups. The fovea capitis was not observed at medial aspect of head and greater tronchanter was ill developed at 2 months of age, later well developed fovea capitis and greater tronchanter were observed in last two groups of animals. The trochlea ridges were not developed till 3 months of age, later it had two equal, parallel and placed almost straight ridges in group-III and IV animals. The medial and lateral condyles were separated by wide intercondyloid fossa.